March. Book three - Lewis, John, 1940 February 21-; Aydin, Andrew; Powell, Nate; Walton, Leigh (2016)
Welcome to the stunning conclusion of the award-winning and best-selling MARCH trilogy. Congressman John Lewis, an American icon and one of the key figures of the civil rights movement, joins co-writer Andrew Aydin and artist Nate Powell to bring the lessons of history to vivid life for a new generation, urgently relevant for today's world.
Keywords: Lewis, John, -- 1940 February 21- -- Comic books, strips, etc; Civil rights movements -- United States -- Comic books, strips, etc; African American legislators -- Biography -- Comic books, strips, etc; Autobiographical comics; Historical comics; Nonfiction comics; Graphic novels; Comics (Graphic works); Autobiographical comics; Comic books, strips, etc; Comics (Graphic works); Graphic novels; Historical comics; Nonfiction comics